Protecting "Killer Crocs" and "Fantasy Football": the Ethics Copyright Law - Frankel, Susy (Victoria University of Wellington Law Review, 1998)
In this article Susy Frankel discusses the iustifications for copyright law which form the ethical basis of copyright protection m New Zealand. It then considers how those justifications are reflected in the case law by examining two Court of Appeal judgments. The author concludes that at times the reasoning and results of individual cases lose sight of the justifications for copyright protection.